QUALITY OF SEED PRODUCED BY TROPICAL FORAGE LEGUMES ON LOW FERTILITY SOILS - Andi L. Amar; Robert A. Congdon; Christopher P. Gardiner; Ross J. Coventry (AGROLAND: The Agricultural Sciences Journal, 2016)
Soil fertility can influence seed production and seedling growth. This study compared seed yields, seed and seedling characteristics of eight forage legumes (Stylosanthesscabra, S. hamata, Centrosemabrasilianum, C. pascuorum, Desmanthuspubescens, D. Virgatus, Macroptiliumbracteatum and M. martii) grown on two soil types (red and yellow kandosols), of low fertility, that are widespread in the Australian tropical rangelands. Seeds of the Desmanthus species germinated most rapidly and, with M. bracteatum, produced the highest proportion of readily germinable seed. M. bracteatum seed produced on the Yellow Kandosol germinated significantly faster, as did the S. hamata from the   Red Kandosol than the other species. S. scabra cv. Seca and C. brasilianum produced   more readily germinable seeds from plants grown on the Red Kandosol. C. pascuorum,     D. pubescens and M. bracteatum produced a higher  percentage of readily germinable seeds and fewer hard seeds when grown on the Yellow Kandosol. No significant differences were found in seedling vigour or biomass allocation from seeds produced on the different soil types